Effects of Noise Frequency on Performance and Well-Being - Sousa, Jorge (2019)
The features of occupational noise, in particular sound pressure levels, the type of noise and its frequency can be related to several physiological and non-physiological effects. However, studies about the influence of occupational noise on non-physiological effects are still scarce. The aim of this study was to investigate effect of intermittent sound patterns with different frequency on subjects’ performance and well-being. Five conditions were simulated and tested through an experimental study: Standard Condition (C0); Industrial noise with alert sounds at 500 Hz (C1); Industrial noise with alert sounds at 1000 Hz (C2); Industrial noise with alert sounds at 2000 Hz (C3); Industrial noise with alert sounds at 3000 Hz (C4). The noise levels were fixed at 45 ± 0.3 dB (A) in C0, and in 68 ± 0.5 dB (A) in the other conditions. The influence of noise on participants’ attention and short-term memory was assessed with the serial recall and response inhibition tests. Discomfort, stress and annoyance were accessed using Visual Analog Scales (VAS). Sixteen undergraduate students were included in this study (8 male; age: M = 22.25 yrs; SD = 0.7 yrs). Higher discomfort, stress and annoyance perceptions were found in condition C4; however, for task performance, no significant differences were found between conditions. This study provided important insights about the influence of different noise frequencies on subject’s performance and well-being. Future research should involve workers and how they react in the field to these conditions.